2016
DOI: 10.1245/s10434-016-5664-7
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Partial Splenectomy for Unknown Primary Cancer: A Stepwise Approach

Abstract: Background. Laparoscopic partial splenectomy (LPS) for focal splenic lesions is technically demanding and carries risk of hemorrhage. Nevertheless, it can be a valuable option, particularly for children and adults in whom attempt at preservation of splenic immunologic function outweighs risk associated with organ preservation. Patient. A 58-year-old man was diagnosed with a focal splenic lesion at the upper splenic pole on surveillance imaging following axillary lymph node metastasis for cancer of unknown prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Forty‐nine publications were selected for review of full text and three duplicate publications, one article undergone LPS for pigs not human, and eight articles that we could not get detailed data were excluded from our review. Forty‐four [5, 6, 11–52] with a total of 252 patients undergoing LPS or LSS met the criteria for analysis. These included four case‐matched comparative studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Forty‐nine publications were selected for review of full text and three duplicate publications, one article undergone LPS for pigs not human, and eight articles that we could not get detailed data were excluded from our review. Forty‐four [5, 6, 11–52] with a total of 252 patients undergoing LPS or LSS met the criteria for analysis. These included four case‐matched comparative studies.…”
Section: Resultsmentioning
confidence: 99%
“…Indications for LPS varied in these series (Table 1). The most common indications in these series were splenic cystic lesions( n = 84) [5, 6, 12–30, 51, 52], followed by splenic hematological diseases ( n = 70) [5, 6, 21, 24, 31, 33–35], non‐cystic intraparenchymal lesions ( n = 59) [5, 6, 20–24, 36–44, 50, 52], spleen rupture ( n = 22) [11, 45], splenomegaly of unknown origin ( n = 9) [5], splenic abscess ( n = 3) [23, 42, 49], severe splenic pain due to ischemia provoked by vascular obstruction of the spleen ( n = 2) [47], and each for Gandy–Gamna bodies, Benign metaplasia, and undiagnosed splenic lesion [22, 48]. The most common surgical procedures performed in these series were four‐trocar laparoscopic splenectomy ( n = 117) [14, 16–18, 20, 22–24, 28, 30, 31, 35, 38, 39, 42, 43, 45, 47, 48, 50, 51], followed by three‐trocar laparoscopic splenectomy ( n = 53) [5, 15,…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we analyzed 39 previously published cases (22 males, 17 females; age range, 33 to 84 years; mean, 64 years) of isolated splenic metastasis derived from CRC (Table 1). [5,8,10,14,[18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][34][35][36][37][38][39][40][41][42][43][44][45][46] Among them, 35 cases were metachronous metastasis and only 4 cases were synchronous metastasis. Interestingly, in terms of splenic lesions, there were only 4 cases of multiple metachronous splenic metastases, and most cases [34] were solitary.…”
Section: Discussionmentioning
confidence: 99%
“…Lopez Monclova et al[ 4 ] reported 6 cases of laparoscopic metastasis splenectomy, all of which had no postoperative complication sand the total survival time ranged from 2 mo to 11 years[ 4 , 5 ]. In terms of abdominal organ malignancy, laparoscopic surgery does not result in higher surgical complications than traditional laparotomy[ 6 ]. Therefore, laparoscopic total splenectomy is safe, reproducible and results in a faster postoperative recovery than traditional surgery.…”
Section: Treatmentmentioning
confidence: 99%